The library users' perceptions of relevance to the information content of a document from different document representation - Paglicawan, Maricar V. (2002)
Document representations are the immediate tools used by library users, which provide information about the original documents they represent. This study focused on the most common document representation: catalog entries, abstracts, and index terms.